Morphological features of larvae of Pandalus eous, P. goniurus, and P. tridents (Decapoda, Pandalidae) from planktonic samples taken in marine waters near Kamchatka Peninsula - Sedova, Nina; Grigoriev, Sergey (Zootaxa, 2017)
Sedova, Nina, Grigoriev, Sergey (2017): Morphological features of larvae of Pandalus eous, P. goniurus, and P. tridents (Decapoda, Pandalidae) from planktonic samples taken in marine waters near Kamchatka Peninsula. Zootaxa 4268 (3): 301-336, DOI:10.11646/zootaxa.4268.3.1